(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the incidence of concomitant osteochondral lesions of the talus (OLT) and their effect on clinical outcome in anterolateral impingement syndrome (ALIS).Materials and Methods: Patients who underwent ankle arthroscopy due to ALIS of the ankle between 2012 and 2018 were retrospectively screened. The patients were divided into two groups according to the presence of OLT. Preoperatively hindfoot alignment (HA) was measured on long axial view radiographs. All measurements were performed by the experienced musculoskeletal radiologist. The association between osteochondral lesions of the talus and hindfoot alignment disorder was statistically assessed. The patients before and after surgery were evaluated with American Orthopedic Foot and Ankle Society (AOFAS) Hindfoot score for clinical performance.Results: OLT accompanied impingement syndrome in 38 (34.8%) of 109 patients examined. The preoperative and postoperative AOFAS Pain and AOFAS Function results were found no significantly different between the two groups according to the presence of OLT (n.s.). However, AOFAS Alignment results of OLT (-) Group were significantly higher than OLT (+) Group. Mean Hindfoot Angle (HA) was −3.7 ± 12.8 (varus) and 4.6 ± 11.2 (valgus) in feet with and without OLT, respectively (Table 1). In this study, there was a significant association between positive OLT and clinical varus hindfoot (p .001)Conclusion: In the current study the hindfoot alignment showed association with the location of OLT in Anterolateral Impingement Syndrome. However, it was also determined that the presence of chondral damage had no negative effect on the treatment of anterolateral impingement syndrome. It should be kept in mind that this syndrome can be accompanied by osteochondral lesions of the talus at a significant rate.